2006
DOI: 10.1159/000092769
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Ischemic Effect of Metoprolol in Patients with Chronic Angina Pectoris Is Gender-Specific

Abstract: Several gender-specific differences in cardiovascular diseases are known and pharmacokinetics of β-blockers shows relevant sex-specific differences. The plasma levels of metoprolol, for example, are higher in women compared to men. However, randomized studies have shown that metoprolol has little or no greater reduction in the mortality of women following myocardial infarction. We tested the hypothesis that metoprolol might have significant gender-specific effects in patients with chronic angina pectoris. Body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Therefore, women may require lower-than-standard doses to avoid adverse effects, whereas men may require larger doses to obtain therapeutic benefit. 38 On the other hand, Cocco et al 39 reported a sex-specific difference in the ischemic effect of metoprolol, specifically that metoprolol showed a favorable effect in men but not in women in spite of a presumed higher plasma concentration of metoprolol in women. They demonstrated that the hemodynamic effects (reduction of blood pressure and heart rate) in men lead to a longer duration of exercise and increased time to angina, ST depression and total metabolic equivalents during exercise, which could reflect a better anti-ischemic effect in men.…”
Section: Diuretic Agents: Torasemidementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, women may require lower-than-standard doses to avoid adverse effects, whereas men may require larger doses to obtain therapeutic benefit. 38 On the other hand, Cocco et al 39 reported a sex-specific difference in the ischemic effect of metoprolol, specifically that metoprolol showed a favorable effect in men but not in women in spite of a presumed higher plasma concentration of metoprolol in women. They demonstrated that the hemodynamic effects (reduction of blood pressure and heart rate) in men lead to a longer duration of exercise and increased time to angina, ST depression and total metabolic equivalents during exercise, which could reflect a better anti-ischemic effect in men.…”
Section: Diuretic Agents: Torasemidementioning
confidence: 99%
“…They demonstrated that the hemodynamic effects (reduction of blood pressure and heart rate) in men lead to a longer duration of exercise and increased time to angina, ST depression and total metabolic equivalents during exercise, which could reflect a better anti-ischemic effect in men. Cocco et al 39 indicated that we need to consider the sex-specific therapeutic effect of metoprolol and that it should be dosed according to the effect on the individual patient rather than according to fixed recommendations.…”
Section: Diuretic Agents: Torasemidementioning
confidence: 99%
“…This may be an important mechanism for the protective effect of metoprolol on reduction of SCD risk after MI. However, it is noted that metoprolol has extensive pharmacological action [35, 36]; the mechanisms underlying improving electrical remodeling certainly included other important factors independent of nerve sprouting, such as adrenergic blockade and ion channel remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…62,63 With regard to pharmacodynamics, aspirin more potently inhibits platelet aggregation 64 and b-blockers more efficiently reduce exerciseinduced angina in men. 65 Of note, women have a 1.5-to 1.7-fold greater incidence of adverse drug reactions than men. 62,63 Indeed, inadequate consideration of sex differences in pharmacokinetics and pharmacodynamics may have serious consequences: Of 10 prescription drugs withdrawn from the market in the United States between 1997 and 2001, 8 posed greater health risks for women, including mibefradil dihydrochloride (PosicorÒ, Roche Laboratories, Nutley, NJ), which was approved for treatment of hypertension and angina and increased the risk for severe bradycardia, especially among elderly women.…”
Section: Sex and Gender Differences In Pharmacological Managementmentioning
confidence: 99%